Deformation-assisted diffusion for the enhanced kinetics of dynamic phase transformation. Issue 11 (2nd November 2018) - Zhao, Lijia; Park, Nokeun; Tian, Yanzhong; Shibata, Akinobu; Tsuji, Nobuhiro
ABSTRACT: Comparison on the kinetics of two different phase transformations, including phase transformation after deformation and phase transformation during deformation (i.e. dynamic transformation, DT), reveals a new discovery that the transformation kinetics can be significantly enhanced in DT even under low driving forces. DT enables continuous generation of defects (e.g. dislocations) near the phase boundary, which can act as short-circuiting diffusion paths for atoms. The diffusivity of atoms is enhanced and the activation energy for the atom jump across the phase boundary is lowered under stress during DT, resulting in more pronounced grain growth as well as accelerated transformation kinetics. GRAPHICAL ABSTRACT: Impact Statement: Deformation-enhanced grain growth is revealed in dynamic phase transformation, which will promote microstructure and property design of structural materials where phase transformations occur.